Thermal Safety Research of Lithium-Ion Batteries Based on Flame-Retardant Phase Change Materials - Jiaxin Zhang; Jiajun Zhao; Yin Chen; Mingyi Chen (Batteries)
Pure phase change materials (PCMs) have drawbacks such as low thermal conductivity and poor physical properties like flammability, which limit their further application in battery thermal management systems. This paper introduces an innovative flame-retardant composite phase change material (CPCM) made from paraffin, expanded graphite, chitosan (CS), ammonium polyphosphate (APP), and aluminum hypophosphite (AHP). The physicochemical properties and flame-retardant performance of CPCMs with five different flame-retardant ratios of 9%, 12%, 15%, 18%, and 21% are studied, and their application effects in battery thermal safety are revealed. The results show that the combination of flame retardants CS, APP, and AHP exhibits effective synergistic effects, and the prepared CPCM exhibits good flame-retardant properties and thermal management effects. The CPCM exhibits outstanding thermal management performance when the flame-retardant content is 12%. At a maximum discharge rate of 3C, compared to natural air-cooling conditions, the maximum battery temperature and temperature difference are controlled within the safe range of 41 °C and below 5 °C, respectively. The CPCM can play an important role in the thermal safety of lithium-ion batteries.